SERVING TWO MASTERS: SKOPOSTHEORIE AND ETHNOLINGUISTIC TRANSLATION ORIENTATION - Harris Hermasnyah Setiajid (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2023)
The skopostheorie and ethnolinguistic translation orientation are two important concepts in the field of translation studies. The skopostheorie, first introduced by Hans J. Vermeer, focuses on the functional aspect of translation, specifically on the communicative purpose or "skopos" of a translation. This theory posits that the purpose of a translation is what determines its appropriate form and content. In other words, the skopos of a translation guides the translator in choosing the best way to convey the source text in the target language. On the other hand, ethnolinguistic orientation refers to the cultural and linguistic factors that influence a translator's decision-making process. It highlights the importance of considering the target audience's cultural background and linguistic expectations when translating a text. This orientation recognizes that translation is not just a linguistic process, but also a cultural one, and that the target audience's culture and language should play a crucial role in determining the appropriate form and content of the translation. The combination of these two theories provides a comprehensive framework for translation, as it considers both the functional and cultural aspects of the translation process. The skopostheorie ensures that the translator has a clear understanding of the communicative purpose of the translation, while the ethnolinguistic orientation ensures that the translation takes into account the cultural and linguistic expectations of the target audience. In conclusion, the skopostheorie and ehnolinguistic translation orientation are essential concepts for translators, as they provide a comprehensive framework for understanding the translation process. By considering both the functional and cultural aspects of translation, translators can ensure that their work is both effective and culturally sensitive, and that the target audience can understand and appreciate the translated text.